Cell density-dependent growth of Myxococcus xanthus on casein. - Rosenberg, E (1977)
When Myxococcus xanthus FB was grown on 0.2% casein it exhibited a phenomenon we call cooperative growth. That is, above 104 cells per ml, both strains that were studied exhibited increasing growth rates as a function of increasing cell numbers. Between 104 and 107 cells per ml, the mean doubling times of strains YS and TNS decreased from 15.2 to 8 h and 26 to 8.5 h, respectively. The extracellular proteinase activity of the two strains was equivalent and directly proportional to cell number. Cooperative growth was correlated with increased concentration of hydrolyzed casein in the medium, suggesting cooperative hydrolysis of casein. At low cell densities neither strain was capable of measurable growth on casein in liquid media, and we have calculated that the average concentration of hydrolyzed casein in the medium was indeed too low to support growth. At low cell densities, growth on hydrolyzed casein (Casitone) was normal and independent of cell concentration. Demonstration of cooperative growth at higher cell densities supports the suggestion that the communal behavior of myxobacteria results in more efficient feeding.